3a - 2b
No. 7b - 2b = 5b
8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3
20a plus 14 will be 34a minus 8a minus 7 34a minus 8 is 26a minus 7 is 19a. The single b is 1b plus 6b which is 7b minus 2b equals 5b.
It is an expression that can be simplified to: 3a-2b+c
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
5b plus 5-3b-7 is 2b-2.
3a - 2b
3a + 5b - 6a - 9b = -3a - 4b
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
It is: 7b+10 simplified
We can combine the like terms. So the b2 can be combined with the 2b2 to give 3b2. Likewise the 3b plus the -5b gives -2b.Therefore, b2 + 3b - 5b + 2b2 = 3b2 - 2b.
a + 7b + 2c
10a+7b undefined variables cannot be determined
They are like terms and can be added simply as 5b
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4
5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0
-2b+8-4b = -5-11b+7 -2b-4b+11b = -5+7-8 5b = -6 b = -6/5
5b + 5b = 2 x 5b
-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b